From the colonial to the contemporary : images, iconography, memories, and performances of law in India's high courts - Khorakiwala, Rahela (Oxford : Hart, 2020)
"From the Colonial to the Contemporary explores the representation of law, images and justice in the first three colonial high courts of India at Calcutta, Bombay and Madras. It is based upon ethnographic research work and data collected from interviews with judges, lawyers, court staff, press reporters and other persons associated with the courts. Observing the courts through the in vivo, in trial and practice, the book asks questions at different registers, including the impact of the architecture of the courts, the contestation around the renaming of the high courts, the debate over the use of English versus regional languages, forms of addressing the court, the dress worn by different court actors, rules on photography, video recording, live telecasting of court proceedings, use of CCTV cameras and the alternatives to courtroom sketching, and the ceremony and ritual that exists in daily court proceedings. The three colonial high courts studied in this book share a recurring historical tension between the Indian and British notions of justice. This tension is apparent in the semiotics of the legal spaces of these courts and is transmitted through oral history as narrated by the judges, lawyers and court staff who are interviewed. The contemporary understandings of these court personnel are therefore seen to have deep historical roots. In this context, the architecture and judicial iconography of the high courts helps to constitute, preserve and reinforce the ambivalent relationship that the court shares with its own contested image"--
Framing the Research -- The Visual Field of Law -- The Calcutta High Court -- The Bombay High Court -- The Madras High Court -- Attributes of Justice -- Conclusion.
Based on author's dissertation (doctoral - Jawaharlal Nehru University, 2017).
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: India. -- High Court (Chennai, India); India. -- High Court (Kolkata, India); India. -- Bombay High Court; Justice, Administration of -- Social aspects -- India; Conduct of court proceedings -- India; Symbolism in law -- India; Courthouses -- India; Law; Electronic books